The hippocampus is not a geometric module: processing environment geometry during reorientation - Sutton, Jennifer E.; Newcombe, Nora S. (Frontiers in Human Neuroscience, 2014)
The hippocampus has long been known to play a role in allocentric spatial coding, but its specific involvement in reorientation, or the recalibration of a disrupted egocentric spatial representation using allocentric spatial information, has received less attention. Initially, the cognitive literature on reorientation focused on a “geometric module” sensitive to the shape formed by extended surfaces in the environment, and the neuroscience literature followed with proposals that particular MTL regions might be the seat of such a module. However, with behavioral evidence mounting that a modular cognitive architecture is unlikely, recent work has begun to directly address the issue of the neural underpinnings of reorientation. In this review, we describe the reorientation paradigm, initial proposals for the role of the MTL when people reorient, our recent work on the neural bases of reorientation, and finally, how this new information regarding neural mechanism helps to re-interpret and clarify the original behavioral reorientation data.